Muscle strength: development of predictive equation for handgrip strength in older adults on the primary health care - Sena Pereira, Maria Luiza Amorim (2023)
Introduction: Monitoring the functional capacity of older adults is fundamental, and Handgrip Strength (HGS) is a consolidated marker of functional status in this age group. This study aimed to develop equations for predicting HGS in community-dwelling older adults in Primary Health Care (PHC). Methods: It is a cross-sectional study conducted with 316 older adults, in which a Multiple Linear Regression (MLR) was performed for the right hand (R-HGS) and left hand (L-HGS). The variables sex, age, weight, knee height (KH), arm circumference (AC), triceps skinfold (TSF), and calf circumference (CC) were considered predictors because they were easily obtained in PHC and significantly related to HGS. Results: In the final models, the variables sex, age, and KH together explained more than 50 % of the HGS variation. There was agreement between the estimated and measured HGS measurements, both for right and left side. Conclusions:  It is concluded that the variability of HGS can be explained by age, sex, and KH, which are parameters simple and routinely used to evaluate older adults.